2019
DOI: 10.1139/cjpp-2018-0604
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen: potential in mitigating oxidative-stress-induced radiation injury

Abstract: Uncontrolled production of oxygen and nitrogen radicals results in oxidative and nitrosative stresses that impair cellular functions and have been regarded as causative common denominators of many pathological processes. In this review, we report on the beneficial effects of molecular hydrogen in scavenging radicals in an artificial system of •OH formation. As a proof of principle, we also demonstrate that in rat hearts in vivo, administration of molecular hydrogen led to a significant increase in superoxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 67 publications
0
52
0
Order By: Relevance
“…We reported similar changes in rats, where H 2 prevented irradiationinduced increases in TNF-α and MDA. But when H 2 was administered alone, TNF-α initially increased above control, and then decreased and remained below both the irradiated group and the non-irradiated control, whereas MDA tended to initially decrease then increase (Kura et al 2018).…”
Section: )mentioning
confidence: 82%
See 1 more Smart Citation
“…We reported similar changes in rats, where H 2 prevented irradiationinduced increases in TNF-α and MDA. But when H 2 was administered alone, TNF-α initially increased above control, and then decreased and remained below both the irradiated group and the non-irradiated control, whereas MDA tended to initially decrease then increase (Kura et al 2018).…”
Section: )mentioning
confidence: 82%
“…Furthermore, pretreatment of SH-SY5Y cells with H 2 protected them from subsequent oxidative stress induced by H 2 O 2 (Murakami et al 2017). In this case, H 2 acted as a mitohormetic effector by transiently increasing mitochondrial superoxide production, followed by an upregulation of Nrf2 transcription D r a f t and induction of other cytoprotective phase II proteins (Murakami et al 2017;Kura et al 2018).…”
Section: )mentioning
confidence: 95%
“…1 Molecular hydrogen modulates signal transduction, protein phosphorylation cascades, gene expression, autophagy, miRNA expression, as well as has important metabolic effects. 5,6 H 2 can induce the Keap1/Nrf2 signaling pathway, 7 promote mitochondrial biogenesis, 8 and the cytoprotective mitochondrial unfolded protein response. 9 H 2 has been proposed to act as an exercise mimetic and redox adaptogen via activating hormetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular hydrogen (H 2 ) has been regarded as a novel therapeutic medical gas since the 2007-Nature Medicine publication [7]. Its potential benefits has been reported in various disease models, including cardiovascular and metabolic diseases [8], brain injury [9], inflammatory disease [10], ocular disease [11], radiation injury [12], cancer [13], and so on. We previously showed that hydrogen inhalation could effectively suppress GBM tumor growth via induction of GSCs differentiation [14].…”
Section: Introductionmentioning
confidence: 99%